PROGRAM MAKAN BERGIZI GRATIS SEBAGAI AGENDA PEMBANGUNAN SDM: ANALISIS IMPLEMENTASI KEBIJAKAN DAN KAPASITAS ADMINISTRASI PUBLIK - Arya Nanda Karyono; Aloisius Sado; Islugin Islugin; Mustafa Kamil (Jurnal Multidisipliner Kapalamada, 2026)
Indonesia's Free Nutritious Meals (MBG) Program is designed to improve public health, learning outcomes, and productivity through adequate nutritional intake. This study aims to examine the implementation of the MBG policy from the perspective of public administrative capacity. A descriptive qualitative approach was employed using policy document analysis and secondary data collected from the National Nutrition Agency, the Ministry of Finance, the Ministry of Health, Statistics Indonesia, the OECD, the World Bank, and the World Food Programme. The analysis was based on the frameworks of policy implementation, administrative capacity, policy capacity, and human capital development. The findings indicate that the existing regulatory framework, technical guidelines, and institutional arrangements provide a strong foundation for program implementation. However, effective implementation requires strengthened operational capacity, integrated beneficiary data systems, food safety monitoring, cross-sectoral coordination, evidence-based evaluation, independent audits, and adaptive policy learning to enhance the program's effectiveness, accountability, sustainability, and long-term contribution to Indonesia's human capital development.